John Henry - Lester, Julius, 1939-2018.; Pinkney, Jerry (New York : Dial Books, 1994)
Retells the life of the legendary African American hero who raced against a steam drill to cut through a mountain.
Keywords: Henry, John -- (Legendary character) -- Legends; Henry, John -- (Legendary character); African Americans -- Folklore; Folklore -- United States